Effect of Moringa oleifera Leaf Extract on Liver and Kidney Histopathology of Sodium Nitrite-Induced Male Rats (Rattus norvegicus) - Niken Ayu Prachelia Putri Niken Ayu Prachelia; Lucya Rahayu Putri Lucya Rahayu; Elsa Yuniarti Elsa; Moralita Chatri Moralita; Siska Alicia Farma Siska Alicia; Yuni Ahda Yuni; Yusni Atifah Yusni (Frontiers on Healthcare Research, 2026)
Background: Sodium nitrite (NaNO2) is a widely used meat preservative that, despite its regulatory approval, can generate reactive oxygen species (ROS) and induce oxidative damage to the liver and kidneys when consumed in excess. This study aimed to determine the effect of Moringa oleifera leaf extract on the liver and kidney histopathology of sodium nitrite-induced male rats (Rattus norvegicus) and to identify the extract dose with the greatest effect. Methods: This experimental study used a completely randomized design with 25 male rats allocated to five groups of five: a negative control (no induction), a positive control induced with sodium nitrite (37.5 mg/kgBW), and three treatment groups given Moringa leaf extract at 200, 400, and 600 mg/kgBW after nitrite induction. Histopathological slides of the liver and kidney were prepared by the paraffin method, stained with hematoxylin-eosin, and examined under a light microscope at 400× magnification. Results: Moringa oleifera leaf extract had a significant effect on the liver and kidney histopathology of the sodium nitrite-induced male rats, and the extent of histological recovery differed across doses. Conclusion: Among the doses tested, 600 mg/kgBW (P3) produced the greatest improvement in the liver and kidney histopathology of the sodium nitrite-induced male rats.